CORPORATE SOCIAL RESPONSIBILITY AS AN INTEGRAL PART OF EFFECTIVE ACTIVITY OF ORGANIZATION - Zi Gunchao (Вестник университета)
Corporate social responsibility (CSR) is a new idea in which the corporate sector incorporates social and environmental issues into its strategies. The reasons, why CSR should become an integral part of the effective activity of the organization: moral obligation, sustainability, license to act and reputation, have been highlighted in the article. The problem of CSR integration into corporate goals has been considered. Integration of business and social needs can provide an organization with a leading position, but this  requires a willingness to make some adjustments. With some effort and foresight, CSR can be easily integrated into the goals of almost all organizations. When properly understood and executed, it is a win-win strategy, that benefits both the company and society.